The Digital History Book Of Semarang City In Learning Text Narrative - Candro Herryka Putra; Nazla Maharani Umaya (Jurnal Pendidikan dan Kebudayaan Missio, 2024)
This study discusses the implementation of digital books containing historical sites in Semarang City in teaching historical narrative texts. Semarang City boasts a variety of historical sites that attract both local and international tourists. In teaching historical narrative texts, the utilization of digital books offers an innovative approach that can enhance students' learning interest and deepen their understanding of local history and cultural heritage. The method employed in this research is qualitative, involving students from class XII IPS at SMA Negeri 8 Semarang. The research findings indicate that the implementation of digital books on historical sites brings about a positive transformation in teaching historical narrative texts by providing a more interactive and immersive learning experience for students. Thus, the integration of digital books on historical sites in teaching historical narrative texts in Semarang City is a crucial step in supporting the understanding, appreciation, and preservation of local historical and cultural heritage.